Kualitas Tidur Anak Usia Sekolah dalam Penggunaan Gadget di Pancoran Mas, Depok - Resi Putri Naulia; Nurbaity Indah Lestari; Muhamad Ridlo (Indonesian Journal of Nursing Scientific, 2021)
Background : One of the factors that can affect a child's sleep quality is electronic factors such as gadgets. The use of gadgets for a long time causes them to live longer than usual. Therefore, these children will tend to sleep later than usual. Objective : To find out the description of the sleep quality of school-age children using gadgets at Pancoran Mas Depok. Methods : This study used a quantitative descriptive design. The sampling technique used was total sampling. Respondents found 33 children in Pancoran Mas Depok. The data were collected using questions collected online and using Microsoft Excel and SPSS version 25. Results : the selection of female respondents was 22 people (66.7%) and the largest number of respondents was 12 years old, which was 14 people (42.4%). ). Respondents who use gadgets at all school age are in the moderate category as many as 33 people (100%). Respondents who have poor sleep quality are 25 children (75.8%). Conclusion: Most of the respondents are female and most of the respondents are at 12 years old. The results also show that all respondents' use of gadgets is in the moderate category and most of the respondents have poor sleep quality. Keywords : Children, sleep quality, gadget users